Efeito da escarificação mecânica e biológica nas propriedades físicas de um latossolo e produtividade da soja em sucessão - Francziskowski, Marcio André (2018)
The clay soils of western Paraná are susceptible to compaction for having a texture and a structure that favor soil reconsolidation after external interventions. Coupled with the adoption of unsuitable or unsustainable agricultural models, soil compaction and degradation are visible and require urgent adoption of corrective practices. Thus, the objective of this research was to assess methods for soil decompaction, as well as mechanical and biological scarification, and to assess the effect of these practices on soil physical properties and soybean crops in succession. The experiment was conducted at State University of Western Paraná’s Experimental Station, located in Entre Rios do Oeste, in a randomized block design, with subdivided plots and four replications. The main plots were characterized by no-tillage and reduced tillage farming, which was performed with a chisel plow. In the subplots, different plant species were cultivated to be used as cover crops – wheat, forage pea consortium with black oats, black oats consortium with forage turnip. After 120 days of sowing, when the cover plants were handled, soil porosity and density, aggregation and aggregate stability, and soil penetration resistance were assessed. Subsequently, the soybean crop was implanted and managed in the experimental area and, at the end of its cycle, the grain yield of the crop was assessed, and so was the physical properties of the soil again. Results showed that mechanical soil scarification for compaction mitigation had a short residual effect, leading to the reconsolidation of the soil structure after nine months of operation, except for reduction of soil penetration resistance. With the cultivation of cover crops, it was possible to observe positive effects on the physical properties of the soil, such as reduced density and increased aeration porosity, which allows the use of these plants in decompaction together with mechanical methods. Mechanical and biological scarification practices did not change the grain yield of the soybean crop in succession.